The Impact of Digital Learning Environments on Student Achievement and Teaching Effectiveness - Humaira Jamela; Thom Myeko (PT Mutiara Bustan Ilmu, 2025)
This study examines the impact of digital learning environments on student achievement and teaching effectiveness. Drawing on a wide range of recent findings, the research highlights how the integration of digital tools in education has transformed traditional instructional approaches. Results indicate that digital technologies significantly enhance student engagement, conceptual understanding, and academic performance across educational levels. Personalized and flexible learning enabled by e-learning platforms caters to individual student needs, improving both satisfaction and outcomes. For teachers, the use of interactive tools supports innovative teaching methods and boosts instructional effectiveness. However, challenges such as the digital divide and limited access to resources remain significant barriers. The study also emphasizes the importance of professional development in equipping educators with the necessary digital competencies. Furthermore, hybrid learning models that blend traditional and digital methods are found to improve motivation and outcomes for both students and teachers. In conclusion, while digital learning environments present substantial benefits, addressing access and training issues is essential to fully realize their potential in enhancing educational quality.